Smart Ladder as a Mathematics Learning Media With a STEAM Approach - Hotman Sugeng Ritonga (Jurnal Inovasi Pembelajaran Matematika, 2022)
This article aims to describe the implementation of using smart ladders as a medium for learning mathematics with the STEAM approach. The research method used is descriptive qualitative. The subjects studied were the fourth grade students of SD Islam Terpadu Mutiata Hati, totaling 10 students. Data collection techniques were carried out through interviews and in-depth observations and documentation techniques. The data analysis technique was carried out by using data triangulation and drawing conclusions. The result of the research is to develop a smart ladder learning media which is developed using a STEAM approach, so as to create innovative and fun and meaningful cross-disciplinary learning. Thus, the focus of this article is that researchers focus more on smart ladders as a medium for learning mathematics with the STEAM approach. In this study, researchers went directly to the field for observation.